(untitled) (Canadian Medical Education Journal, 2023)
Background: The transition from residency training into practice is associated with increasing risks of litigation, burnout, and stress. Yet, we know very little about how best to prepare graduates for the full scope of independent practice, beyond ensuring clinical competence. Thus, we explored the transition to independent practice (TTP) experiences of recent Obstetrics and Gynaecology graduates to understand potential gaps in their perceived readiness for practice. Methods: Using constructivist grounded theory, we conducted semi-structured interviews with 20 Obstetricians/Gynaecologists who graduated from nine Canadian residency programs within the last five years. Iterative data collection and analysis led to the development of key themes. Results: Five key themes encompassed different practice gaps experienced by participants throughout their transition. These practice gaps fit into five competency domains: providing clinical care, such as managing unfamiliar low-risk ambulatory presentations; navigating logistics, such as triaging referrals; managing administration, such as hiring or firing support staff; reclaiming personhood, such as boundary-setting between work and home; and bearing ultimate responsibility, such as navigating patient complaints. Mitigating factors were found to widen or narrow the extent to which new graduates experienced a practice gap. There was a shared sense among participants that some practice gaps were impossible to resolve during training. Conclusions: Existing practice gaps are multi-dimensional and perhaps not realistically addressed during residency. Instead, TTP mentorship and training opportunities must extend beyond residency to ensure that new graduates are equipped for the full breadth of independent practice.